The Patterns of Language Usage in Political News on Tempo.co Online Media - Maria Septian Riasanti Mola (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
This research aims to analyze the patterns of language use in political news on the online media Tempo.co using Critical Discourse Analysis (CDA) approach. Two political news articles selected from the period of March 20, 2024, regarding election disputes and congratulations to the election winners, became the focus of analysis. The research method employed a qualitative approach with CDA discourse analysis technique. The findings indicate that political news on Tempo.co employs strong language to construct the political identities of related figures and to convey political messages. Rhetorical strategies such as metaphors and hyperboles are used to strengthen political arguments. Emphasis on controversial political issues is also found in the news. These findings indicate that political media not only serve as sources of information but also as tools for shaping public views and opinions. In conclusion, understanding the language construction in political news is essential to comprehend political dynamics and its influence on society. Keywords:Critical Discourse Analysis, Political News, Online Media, Tempo.co, Political Identity.